Craighead's international business, travel, and relocation guide to 78 countries, 1996-97. - Gale Research Inc. (New York Gale Research, 1995)
Triennial
Includes material from: Craighead's international executive travel and relocation service.
Keywords: Americans -- Employment -- Foreign countries -- Handbooks, manuals, etc; International business enterprises -- Personnel management -- Handbooks, manuals, etc; Travel -- Handbooks, manuals, etc